Glucocorticoids Impair Phagocytosis and Inflammatory Response Against Crohn’s Disease-Associated Adherent-Invasive Escherichia coli - Olivares-Morales, Mauricio Javier; De La Fuente, Marjorie Katherine; Dubois-Camacho, Karen; Parada, Daniela; Diaz-Jiménez, David; Torres-Riquelme, Alejandro; Xu, Xiaojiang; Chamorro-Veloso, Nayaret; Naves, Rodrigo; Gonzalez, Maria-Julieta; Quera, Rodrigo; Figueroa, Carolina; et al. (Frontiers in Immunology, 2018)
Crohn’s disease (CD) is a chronic inflammatory bowel disorder characterized by deregulated inflammation triggered by environmental factors. Notably, adherent-invasive Escherichia coli (AIEC), a bacterium with the ability to survive within macrophages is believed to be one of such factors. Glucocorticoids are the first line treatment for CD and to date, it is unknown how they affect bactericidal and inflammatory properties of macrophages against AIEC. The aim of this study was to evaluate the impact of glucocorticoid treatment on AIEC infected macrophages. First, THP-1 cell-derived macrophages were infected with a CD2-a AIEC strain, in the presence or absence of the glucocorticoid dexamethasone (Dex) and mRNA microarray analysis was performed. Differentially expressed mRNAs were confirmed by TaqMan-qPCR. In addition, an amikacin protection assay was used to evaluate the phagocytic and bactericidal activity of Dex-treated macrophages infected with E. coli strains (CD2-a, HM605, NRG857c, and HB101). Finally, cytokine secretion and the inflammatory phenotype of macrophages were evaluated by ELISA and flow cytometry, respectively. The microarray analysis showed that CD2-a, Dex, and CD2-a + Dex-treated macrophages have differential inflammatory gene profiles. Also, canonical pathway analysis revealed decreased phagocytosis signaling by Dex and anti-inflammatory polarization on CD2-a + Dex macrophages. Moreover, amikacin protection assay showed reduced phagocytosis upon Dex treatment and TaqMan-qPCR confirmed Dex inhibition of three phagocytosis-associated genes. All bacteria strains induced TNF-α, IL-6, IL-23, CD40, and CD80, which was inhibited by Dex. Thus, our data demonstrate that glucocorticoids impair phagocytosis and induce anti-inflammatory polarization after AIEC infection, possibly contributing to the survival of AIEC in infected CD patients.